The Knowledge Transfer Programme of Natural Irrigation System For Indigenous People - Haji Razali, Mohd. Hudzari; Abdullah, Ramle; Haji Muhammad, Hasbullah; Zakaria, Mat (2013)
Agriculture is the backbone of civilization and as stated by a celebrated Islamic scholar An-Nawawi, agriculture is the best career for human being to be in. In Malaysia, agriculture was, and is always an important government agenda to ensure the country food security for the population. To this time, some agricultural modernization has taken place among the indigenous communities through specific government programmes or indirect interface of members of respective societies. This programme aims at looking into the feasibility of direct agricultural knowledge transfer especially natural irrigation to the indigenous people. The basic agricultural knowledge and application, such as irrigation system for agrotechnology will be transferred to the community directly. The activity is to be implemented via integration with JAKIM programme called Ihya Ramadhan and Eidulfitri festival to take advantage on the already established network and the effectiveness of the knowledge transfer programme. This programme offer a tangible content for a mission to the indigenous people in both spiritual and secular necessity. The involvement of Muslim volunteers, both of government servants and private institutions of background in term of expertise create a sense of fulfillment for the agenda of knowledge transfer.